Ready or Not? Oral Health Therapists' Preparedness for Dental Practice in Aotearoa New Zealand - Smith, Jacqui; Han, Heuiwon; Lansdown, Karen (Wiley, 2026)
Introduction The Dental Council of New Zealand requires oral health therapists (OHTs) to meet competency in seven domains to be considered safe to practise clinically in Aotearoa New Zealand (NZ). The aim of this study was to explore OHT graduates' preparedness for clinical practice. Methods OHT graduates from the Auckland University of Technology and the University of Otago from the 2020 to 2023 cohorts were invited to participate in an online survey. The survey used an adapted version of the Dental Undergraduates Preparedness Assessment Scale (DU-PAS) to retrospectively evaluate their self-perceived preparedness to practise at the time of graduation. Results Of 103 responses, 79 were eligible with complete DU-PAS data (response rate of 24.5%). Mean total DU-PAS score was 73.1 ± 13.4; Part A (clinical) mean score was 33.8 ± 8.0, and Part B (behavioural/cognitive) score was 39.3 ± 7.8. Participants reported they performed most clinical procedures independently upon graduation; however, low confidence was recorded in orthodontic auxiliary tasks, amalgam restorations and pulpotomies. Participants also reported confidence in communication, professionalism and confidentiality, while they noted challenges with managing treatment expectations, colleague behaviour, and evaluating new materials and products. Perceived factors that influenced preparedness to practise included clinical placement time, COVID-19, mentorship, and previous dental industry experience. Conclusion This study is the first to evaluate OHTs' preparedness for practice in NZ using a modified DU-PAS tool. Participants perceived themselves to be prepared clinically and cognitively, comparable to international dental counterparts. Despite overall confidence, this study identified clinical and behavioural/cognitive gaps, demonstrating the need for curriculum and practice-based learning improvements to better support OHTs' preparedness for practice.
Keywords: 1105 Dentistry; 1302 Curriculum and Pedagogy; Dentistry; 3203 Dentistry; 3901 Curriculum and pedagogy; clinical competence; curricula development; dental; dental education; DU-PAS; oral health therapist; preparedness for practice; workforce readiness